2017
DOI: 10.1093/humrep/dex087
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin stimulates lipid metabolism via AMPK in rabbit blastocysts

Abstract: STUDY QUESTIONHow does a maternal diabetic hyperadiponectineamia affect signal transduction and lipid metabolism in rabbit preimplantation blastocysts?SUMMARY ANSWERIn a diabetic pregnancy increased levels of adiponectin led to a switch in embryonic metabolism towards a fatty acid-dependent energy metabolism, mainly affecting genes that are responsible for fatty acid uptake and turnover.WHAT IS KNOWN ALREADYAlthough studies in cell culture experiments have shown that adiponectin is able to regulate lipid metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 52 publications
5
34
0
Order By: Relevance
“…In BF, short chain carnitine-bound fatty acids, like acetylcarnitine, 3-hydroxybutyrylcanitine and hexanoylcarnitine, were also increased, indicating impaired embryonic beta-oxidation as well. We have recently shown that CPT1 is increased in blastocysts from diabetic rabbits [43], indicating increased fatty acid oxidation in blastocysts from diabetic rabbits. This result is in line with the observed elevated BHBA levels in maternal plasma and BF due to diabetes mellitus.…”
Section: Diabetic Dysregulation Of Maternal and Embryonic Lipid Metabmentioning
confidence: 94%
See 2 more Smart Citations
“…In BF, short chain carnitine-bound fatty acids, like acetylcarnitine, 3-hydroxybutyrylcanitine and hexanoylcarnitine, were also increased, indicating impaired embryonic beta-oxidation as well. We have recently shown that CPT1 is increased in blastocysts from diabetic rabbits [43], indicating increased fatty acid oxidation in blastocysts from diabetic rabbits. This result is in line with the observed elevated BHBA levels in maternal plasma and BF due to diabetes mellitus.…”
Section: Diabetic Dysregulation Of Maternal and Embryonic Lipid Metabmentioning
confidence: 94%
“…This key phospholipid is an important activator of the p38 MAPK pathway under conditions of cell stress and lipotoxicity [51]. In blastocysts from diabetic rabbits, the p38 MAPK pathway is activated [43], indicating that high 1-stearoyl-2-arachidonoyl-GPC levels activate p38 MAPK pathway in embryonic cells.…”
Section: Diabetic Dysregulation Of Maternal and Embryonic Lipid Metabmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that HMW adiponectin is involved in insulin sensitivity, glucose uptake, and lipid metabolism. Investigative research has reported the involvement of different adiponectin isoforms in the pathogenesis of various diseases [5]. It has also been shown that these isoforms act as acute-phase reactants that influence inflammatory mechanisms in both acute and chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that fat deposition could be decreased by downregulating the expression of lipogenesis pathway genes such as sterol regulatory element-binding protein-1(srebp-1), acetyl-CoA carboxylase α (accα) and fatty acid synthase ( fas), and/ or up-regulation of lipolysis pathway genes such as PPARα ( pparα), hormone-sensitive lipase (hsl) and carnitine palmitoyltransferase 1A (cpt1a) (16)(17)(18)(19) . In addition, adiponectin, a hormone involved in the regulation of glucose metabolism and fatty acid breakdown in mammals, could lower intracellular lipid content (20) . Therefore, dietary supplements that can regulate lipid metabolism or adiponectin and, consequently, reduce excess lipid deposition, alleviate hepatic steatosis and attenuate inflammation response would be highly beneficial.…”
mentioning
confidence: 99%